(untitled) (Raparin Journal of Humanities (RJH), 2025)
The objective of this research paper is to identify the role of producer in the morning television shows in Kurdish satellite channels. This study classified as descriptive research using a survey method to collect data with a specific sample of 84 journalits and individuals working in production of the morning TV shows in Kurdish satellite channels in the Kurdistan region of Iraq. Several key findings emerged from the study, as follows: A majority of the participants perceive the role of a program producer in morning shows as a very challenging and complictaed task. The research conclusion has also demonstrated that the preparation of moring programs requires more effort than is typically anticipated, and it the producer is very significant elemnt for the morning programs. According to the findings the producer’s experiences are plays crucial role to enhance the qualities of TV programs, as they have a substantial impact on the program’s acceptance by the audiences. The study results have indicated that the producers should consider the moring shows’ guests by inviting a diverse group of experts who are well-suited to the chosen topics. Finally, the vast majority of the participants affirmed that the program presenters also should ideally be responsible for program preparation as well, as they possess a deep understanding of the program’s objectives and the preferences of the viewers.